Emerging Trends in Expert Applications and Security Proceedings of ICETEAS 2018 - Rathore, Vijay Singh; Worring, Marcel; Mishra, Durgesh Kumar; Joshi, Amit.; Maheshwari, Shikha; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book covers current developments in the field of expert applications and security, which employ advances of next-generation communication and computational technology to shape real-world applications. It gathers selected research papers presented at the ICETEAS 2018 conference, which was held at Jaipur Engineering College and Research Centre, Jaipur, India, on February 17-18, 2018. Key topics covered include expert applications and artificial intelligence; information and application security; advanced computing; multimedia applications in forensics, security and intelligence; and advances in web technologies: implementation and security issues.
Keywords: Computational intelligence; Data protection; Artificial intelligence; Computational Intelligence; Data and Information Security; Artificial Intelligence